2013
DOI: 10.22230/cjnser.2013v4n2a147
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalism and Homelessness in the Western Canadian Arctic

Abstract: Homelessness in the Beaufort-Delta represents a significant problem that is underserved by government, market, and nonprofit agencies. Based on research conducted during 2011-2012, this article outlines the breadth and scope of the housing problem and details extant service provision networks for homeless and hard-to-house (HtH) persons with addiction and mental health problems. A critique of neoliberal governance on housing development and social services suggests that significant effort is needed to deal wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…These communities act as service centres, or stop-points between resource-extraction sites and larger urban centres. This echoes what is also reported to drive housing affordability in the western Artic (Young and Moses, 2013). Not surprisingly, northern Alberta areas reported a much more intimate link with the oil and gas industry, which was attributed to be a main driver in their homelessness population.…”
Section: Economic Dynamicssupporting
confidence: 74%
See 1 more Smart Citation
“…These communities act as service centres, or stop-points between resource-extraction sites and larger urban centres. This echoes what is also reported to drive housing affordability in the western Artic (Young and Moses, 2013). Not surprisingly, northern Alberta areas reported a much more intimate link with the oil and gas industry, which was attributed to be a main driver in their homelessness population.…”
Section: Economic Dynamicssupporting
confidence: 74%
“…Most noted that homelessness was not only a major challenge to the social infrastructure of their locality, but even noted its prevalence and intensity to be increasing in recent years. This impact on communities is a dynamic that is mentioned (Young & Moses, 2013) but has not been well explored in the literature. Across the 20 study communities, the reported homelessness trends appeared to be closely tied to macro-economic shifts in the global economy impacting Alberta; particularly as related to the oil and gas industry.…”
Section: Economic Dynamicsmentioning
confidence: 99%
“…In Inuvik, NWT, no official homeless 'count' has been made; however, estimates from support providers suggest that visible homelessness affects 40 to 60 people, roughly 1% to 2% of the town's population (Christensen, 2017). More accurate numbers are difficult to obtain, in part because the focus on homelessness in Yellowknife has produced a relative policy blindness to the issue outside the capital region, and in part because services for the homeless in Inuvik are severely lacking, making it difficult to know who would be using those services were they to exist (Young and Moses, 2013).…”
Section: The Canadian Northmentioning
confidence: 99%
“…This is particularly the case among those men, women, and youth who cannot (or for various reasons will not) access space in emergency shelters. Research has also shown that RCMP holding cells in Whitehorse, Yellowknife, Iqaluit, and Inuvik are used as de facto shelters in those communities because existing shelters lack adequate beds and some have a sobriety requirement (Christensen 2012(Christensen , 2017Mechan, 2013;Nunavut Housing Corporation, 2013;Young and Moses, 2013;Young, 2016). The prevalence of hidden forms of homelessness, combined with other coping strategies, adds to the difficulty of assessing homelessness in the North.…”
Section: The Canadian Northmentioning
confidence: 99%
“…Shelters offer services that are intended to transition vulnerable women from homelessness to stable housing through the concurrent provision of necessary health and social services. The coordination and timeliness of appropriate services to break the cyclic nature of homelessness is challenging given the variability and complexity of needs that threaten well-being [11,15].…”
Section: Introductionmentioning
confidence: 99%